2021
DOI: 10.1101/2021.11.24.469908
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expression of mini-G proteins specifically halt cognate GPCR trafficking and intracellular signalling

Abstract: Mini-G proteins are engineered thermostable variants of Gα subunits designed to specifically stabilise G protein-coupled receptors (GPCRs) in their active conformation for structural analyses. Due to their smaller size and ease of use, they have become popular tools in recent years to assess specific GPCR behaviours in cells, both as reporters of receptor coupling to each G protein subtype and for in-cell assays designed to quantify compartmentalised receptor signalling from a range of subcellular locations. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…However, it needs to be taken into account that the miniGα q protein is engineered and may not always represent the physiological situation, despite extensive validation. Indeed, recent research has uncovered that GPCR trafficking and signaling properties may be altered by the expression of miniG proteins (Carpenter & Tate, 2016; Manchanda, 2021; Nehme et al, 2017; Wan et al, 2018). Furthermore, the addition of tags, such as the (fluorescent/luminescent) protein(s) (fragments), can theoretically influence the properties of a protein.…”
Section: In Vitro Functional Assays Monitoring 5‐ht2ar Activationmentioning
confidence: 99%
“…However, it needs to be taken into account that the miniGα q protein is engineered and may not always represent the physiological situation, despite extensive validation. Indeed, recent research has uncovered that GPCR trafficking and signaling properties may be altered by the expression of miniG proteins (Carpenter & Tate, 2016; Manchanda, 2021; Nehme et al, 2017; Wan et al, 2018). Furthermore, the addition of tags, such as the (fluorescent/luminescent) protein(s) (fragments), can theoretically influence the properties of a protein.…”
Section: In Vitro Functional Assays Monitoring 5‐ht2ar Activationmentioning
confidence: 99%
“…We also employed a different approach to quantify plasma membrane and endosomal activity from both incretin receptors based on a NanoBRET assay to measure the recruitment of NanoLuc-fused mini-Gs proteins to either KRAS- or Rab5-Venus constructs (Supplementary Figure 7C). We have recently shown that co-expression of mini-Gs with a cognate GPCR results in the inhibition of the normal level of receptor internalization in response to agonist stimulation [28]. For this reason, we were only able to perform this assay by using supra-physiological levels (100 nM) of GLP-1 and GIP and we could not obtain concentration response curves.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to a BRET pair, the mini-G assay can be adapted to use the NanoLuc complementation assay NanoBiT ( Section 3.3 ) by fusing LgBiT to the mini-G protein and SmBiT to the receptor of interest ( Benkel et al, 2022 ). Although confocal microscopy and BRET spectroscopy have demonstrated mini-G recruitment to GPCRs at internal membranes such as the Golgi and endosomes ( Wan et al, 2018 ), mini-G protein binding to a GPCR have been reported to abolish β-arr recruitment and subsequent receptor internalisation ( Manchanda et al, 2021 ), which, if corroborated, would make them unsuitable to study internalised receptor signalling or biased agonism.…”
Section: Sensors For G-protein-dependent Signal Transductionmentioning
confidence: 99%